Las feromonas y sus usos en el manejo integrado de plagas - Blanco Metzler, H.
(Es, En)
Ilus., 15 ref.
Keywords: FEROMONAS; TRAMPAS SEXUALES; CONTROL BIOLOGICO; ETIOLOGIA; GESTION DE LUCHA INTEGRADA; COSTA RICA